Det gamla släkthuset: Minnen, miljöer och autoetnografi - Meurling, Birgitta (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2015)
For several decades ethnologists have discussed reflexivity and its implications for research. This also often means that the researcher’s personal history and background need to be taken into account when studying other people and their lives. In this article my point of departure is the summerhouse of my family, built in 1907. I spent all my summers during childhood in this house close by the lake, so did my mother, her sister and my grandmother with her brothers and sisters. When entering the garden and the house I am carried away by a flow of memories and nostalgia. The building itself carries messages concerning how to live a good and respectable life. The floor plan reveals how to find your place as a man, a woman, a child or a servant; it tells the story about social hierarchies. Together with family lore, the furniture, equipment and different material objects that were collected for generations back tell you who you are and how you are supposed to behave. My habitus, to use Pierre Bourdieu’s concept, is influenced by these childhood surroundings and experiences and I am still in some ways characterized by them, in my private life as well as in my profession. So, for me the autoethnographical writing is one way to be even more reflexive as a professional ethnologist. It is a challenge, but it is worth a try.